2014
DOI: 10.1021/es503510q
|View full text |Cite
|
Sign up to set email alerts
|

Current Levels and Composition Profiles of Emerging Halogenated Flame Retardants and Dehalogenated Products in Sewage Sludge from Municipal Wastewater Treatment Plants in China

Abstract: Occurrence of new toxic chemicals in sludge from wastewater treatment plants (WWTPs) is of concern for the environment and human health. Alternative halogenated flame retardants (HFRs) are a group of potentially harmful organic contaminants in the environment. In this study, a nationwide survey was carried out to identify the occurrence of HFRs and their potential dehalogenated products in sewage sludge from 62 WWTPs in China. Of all 20 target chemicals analyzed, decabromodiphenyl ethane (DBDPE), hexabromocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 60 publications
5
55
0
Order By: Relevance
“…De la Torre et al (2011) reported higher levels of DP in sewage sludge from 31 urban Spanish wastewater treatment plants (WWTP), and a significant positive correlation (r = 0.619, p b 0.05) was found between DP concentrations with the contribution of industrial input to waste streams. Zeng et al (2014) also found relatively higher levels of DP in sewage sludge from the eastern China, especially in coastal areas where the urbanization and industrialization level is higher. In the residential indoor dust in the city of Ottawa, DP levels ranged from 2.3 to 5683 ng g −1 , which were comparable to the levels in dust from Stockholm (b 0.19-4800 ng g − 1 ) (Newton et al, 2015), but were several times higher than those in the sediment of the Great Lakes (Zhu et al, 2007).…”
Section: Urban/industrial Activitymentioning
confidence: 76%
See 4 more Smart Citations
“…De la Torre et al (2011) reported higher levels of DP in sewage sludge from 31 urban Spanish wastewater treatment plants (WWTP), and a significant positive correlation (r = 0.619, p b 0.05) was found between DP concentrations with the contribution of industrial input to waste streams. Zeng et al (2014) also found relatively higher levels of DP in sewage sludge from the eastern China, especially in coastal areas where the urbanization and industrialization level is higher. In the residential indoor dust in the city of Ottawa, DP levels ranged from 2.3 to 5683 ng g −1 , which were comparable to the levels in dust from Stockholm (b 0.19-4800 ng g − 1 ) (Newton et al, 2015), but were several times higher than those in the sediment of the Great Lakes (Zhu et al, 2007).…”
Section: Urban/industrial Activitymentioning
confidence: 76%
“…Chromatographic separation was usually achieved using capillary gas chromatography (GC) columns with a non-polar stationary phase, such as DB-5MS (De la Hoh et al, 2006;Jia et al, 2011;Ren et al, 2008;Zeng et al, 2014;Zhang et al, 2013;Zheng et al, 2015a), DB-5HT (Muñoz-Arnanz et al, 2011), DB-XLB (Chen et al, 2013a(Chen et al, , 2013bMo et al, 2013;Yan et al, 2012;Zhang et al, 2011b), CP-Sil 13 CB , VF-5MS (Peng et al, , 2014, Rxi-5MS (Qiu and Hites, 2008) and Rtx-1614 (Ben et al, 2013;Peverly et al, 2015). The 15 m and 30 m columns were generally selected.…”
Section: Instrumental Analysis and Quantificationmentioning
confidence: 99%
See 3 more Smart Citations